ANALISIS DEIKSIS PADA TEKS BERITA MEDIA DARING TVONENEWS.COM SEPUTAR HEWAN KURBAN - Ratu Mashruhah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
The purpose of this study is to explain how to use deixis of persona, place, and time in news texts about sacrificial animals on tvonenews.com website. This research uses a qualitative descriptive approach, which collects data through observation, recording, and documentation. Facts were collected from the news texts published on the website. The results show that in the news texts there is the use of words and phrases to describe deixis of persona, place, and time. Data analysis resulted in 12 examples of deixis usage, with 5 examples focusing on persona, 2 examples on time, and 5 examples on place.